FORMATION OF ORGANIC COMPOUNDS DURING BACTERIAL OXIDATION OF FLOTATION CONCENTRATE - Umirqulova, M.V; Qodirov, A.U (Innovative Development in Educational Activities, 2023)
The article deals with the behavior of the most important cationic elements, which directly affect the processes of bacterial oxidation of sulphide ores. These are iron, calcium, selenium, arsenic, various modifications of sulfur. In addition to this, data are presented on the appearance of new compounds that promote the dissolution of precious metals, which are selenites, thiosulfates, hydrochloric acid and nitric acid. The questions of the behavior of organic carbon, the possibility of its activation and the ability to absorb noble metals are covered.